Impact of Motivational Factors on Employee Turnover Intention in Taj Samudra, Colombo (Global Journal of Management and Business Research, 2019)
Employee turnover has been an everlasting problematic function in any business organization or for an industry. Taj Samudra is a leading luxury hotel in the Colombo city which is continuously going through a similar problem from past few months. The Turnover and the turnover intention of the organization has the management left with no option but to find solutions to overcome this situation immediately. In this research the author would like to ident ify the impact of performance management on the turnover intention of the Taj employees, the sample size would be taken as 60 out of 600 employees. The objectives of this research would to identify the different variables impacting the turnover intention such as performance management, working culture, monetary benefits and rewards and recognition. Also finding prevailing issues in the performance management system and find suitable recommendations to overcome any deviations of the current Performance management system.
Keywords: motivational factors/working culture/monetary benefits/leadership style/rewards